2020
DOI: 10.1097/mnh.0000000000000646
|View full text |Cite
|
Sign up to set email alerts
|

Pain management in patients with chronic kidney disease and end-stage kidney disease

Abstract: Purpose of Review-This review evaluates current recommendations for pain management in CKD and ESKD with a specific focus on evidence for opioid analgesia, including the partial agonist, buprenorphine.Recent Findings-Recent evidence supports the use of physical activity and other nonpharmacologic therapies, either alone or with pharmacological therapies, for pain management. Nonopioid analgesics, including acetaminophen, topical analgesics, gabapentinoids, serotonin-norepinephrine reuptake inhibitors, and tric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
21

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 124 publications
0
22
0
21
Order By: Relevance
“…Our study on more contemporary prescribing patterns found that patients on hemodialysis were prescribed on average approximately 7 medications per day. Our findings of an overall slight decrease in the number of medications over time likely reflects the incorporation of updated guidelines and recommendations, and greater awareness among clinicians regarding medication management safety [11], efforts to improve medication management [37-40], and address pain management with nonopioid analgesics [41, 42]. We found that the prescribing of harmful medications decreased in the overall population and across subgroups by age, sex, race, and LIS status.…”
Section: Discussionmentioning
confidence: 84%
“…Our study on more contemporary prescribing patterns found that patients on hemodialysis were prescribed on average approximately 7 medications per day. Our findings of an overall slight decrease in the number of medications over time likely reflects the incorporation of updated guidelines and recommendations, and greater awareness among clinicians regarding medication management safety [11], efforts to improve medication management [37-40], and address pain management with nonopioid analgesics [41, 42]. We found that the prescribing of harmful medications decreased in the overall population and across subgroups by age, sex, race, and LIS status.…”
Section: Discussionmentioning
confidence: 84%
“…Selected large retrospective studies are summarized in Table 1. Pain management in patients with end‐stage kidney disease requires experience in using NSAIDs and these opioids, which seem to be the safest for the kidney function, including buprenorphine, fentanyl, hydromorphone methadone, and oxycodone 48 …”
Section: Discussionmentioning
confidence: 99%
“…Paracetamol is safe to use in patients with ESRF and may be used without dose adjustment, but long-term use can cause analgesic nephropathy [ 149 ].…”
Section: Postoperative Carementioning
confidence: 99%
“…Some analgesics, such as lidocaine and capsaicin, can be applied as patches, and are safe and effective in the treatment of acute and chronic pain when used in a limited area. This approach provides localized analgesia in patients with kidney disease [ 149 ].…”
Section: Postoperative Carementioning
confidence: 99%